Relationship of Muna Language, Ciacia, Tukang Besi and Culambacu (Lexicostatistic and Glotochronology Study) - La Ino; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2021)
This article is motivated by the results of the 2019 SIL research that the languages ​​in Southeast Sulawesi Province vary in category. Some are strong and some are threatened. Among the languages ​​that are categorized as threatened are the Muna language, the Ciacia language, while the Tukang Besi language is included in the strong language group. However, there are still several languages ​​that have not been listed in the SIl research, namely the Culamabacu language. This article discusses the kinship between the Muna language, Ciacia language, the Tukang Besi language and the Culambacu language. This paper uses the theory of comparative historical linguistics with lexicostatistical and glotochronological methods. The results of the analysis of the four languages ​​are that the percentage of Muna and Ciacia language kinship is 49%, Muna language kinship with Tukang Besi 43%, Muna language with Culambacu language 36%, Ciacia language with Tukang Besi 43%, Ciacia language with Culambacu language is 37%, the Tukang Besi language is with Culambacu language 33%. Based on the glottochronology, the Ciacia language and Muna language have a separate year of 1912-1532, the Ciacia language and the Tukang Besi language have a separate year of 2279-183, the Ciacia language and Culambacu language have the years 2587-2211, the Muna language and the Tukang Besi language have a 2371-2335 year, Muna language with Culambacu language has the years 2658-2272, the Tukang Besi language with Culambacu language has a separate year 2885-2465.